Why Are "Others" So Polarized? Perceived Political Polarization and Media Use in 10 Countries. Issue 5 (13th September 2016) - Yang, JungHwan; Rojas, Hernando; Wojcieszak, Magdalena; Aalberg, Toril; Coen, Sharon; Curran, James; Hayashi, Kaori; Iyengar, Shanto; Jones, Paul K.; Mazzoleni, Gianpietro; Papathanassopoulos, Stylianos; Rhee, June Woong; et al.
Abstract: This study tests the associations between news media use and perceived political polarization, conceptualized as citizens' beliefs about partisan divides among major political parties. Relying on representative surveys in Canada, Colombia, Greece, India, Italy, Japan, South Korea, Norway, the United Kingdom, and the United States, we test whether perceived polarization is related to the use of television news, newspaper, radio news, and online news media. Data show that online news consumption is systematically and consistently related to perceived polarization, but not to attitude polarization, understood as individual attitude extremity. In contrast, the relationships between traditional media use and perceived and attitude polarization is mostly country dependent. An explanation of these findings based on exemplification is proposed and tested in an experimental design.